2018
DOI: 10.3389/fnagi.2018.00032
|View full text |Cite
|
Sign up to set email alerts
|

Increased Degradation Rates in the Components of the Mitochondrial Oxidative Phosphorylation Chain in the Cerebellum of Old Mice

Abstract: Brain structures differ in the magnitude of age-related neuron loss with the cerebellum being more affected. An underlying cause could be an age-related decline in mitochondrial bioenergetics. Successful aging of mitochondria reflects a balanced turnover of proteins involved in mitochondrial biogenesis and mitophagy. Thus, an imbalance in mitochondrial turnover can contribute to the diminution of cellular function seen during aging. Mitochondrial biogenesis and mitophagy are mediated by a set of proteins inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 59 publications
(69 reference statements)
0
14
0
Order By: Relevance
“…The use of stable isotope labeling in conjunction with LC-MS/MS has opened the door for analyses of protein turnover kinetics on a global scale (4,9,17,18,29). In a number of model systems, proteomic studies have shown that aged individuals have significantly slowed protein turnover compared to younger counterparts (30)(31)(32), although this effect may not be universal and appears variable for different proteins, tissues and organisms (33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…The use of stable isotope labeling in conjunction with LC-MS/MS has opened the door for analyses of protein turnover kinetics on a global scale (4,9,17,18,29). In a number of model systems, proteomic studies have shown that aged individuals have significantly slowed protein turnover compared to younger counterparts (30)(31)(32), although this effect may not be universal and appears variable for different proteins, tissues and organisms (33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…One such ubiquitination target of Parkin is HIF-1, and Parkin expression was very recently shown to have an inverse correlation with both HIF-1 levels and metastasis in human breast cancer tissue [30]. As mentioned previously, with aging comes increased dysfunction in mitochondrial ETC proteins; imbalanced turnover has also been noted in proteins involved in the mitophagy process, for example in the mouse cerebellum [31] and aging skeletal muscle from several mammals [32]. An area of continued focus regarding the Parkin/PINK1 pathway are its roles in regulating basal mitophagy/proteostasis as opposed to activation only in response to a stress signal.…”
Section: Cellular Proteome Imbalance Results Through Numerous Mechanimentioning
confidence: 99%
“…Popa-Wagner et al [ 62 ] have shown that the turnover rates for DMN1l and FIS1, which are proteins implicated in mitochondrial biogenesis, mitophagy, and fission go in opposite directions in the cerebellum of 22-month-old C57BL6j mice when compared to three-month-old mice. Unlike previous studies that have reported decreased turnover rates for the mitochondrial respiratory complexes of aged rodents, the authors found increased turnover rates for mitochondrial proteins of the oxidative phosphorylation chain in the aged mice when compared to young mice.…”
Section: Latest Findingsmentioning
confidence: 99%